Effect of Investment Decisions, Capital Structure, Profit Management, Cash Flow of Corporate Social Resposibility Reporting, Financial Performance and Value of Manufacturing Companies Listed in Indonesia Stock Exchange - Attarie, Prima Noermaning; Ratnawati, Tri; Moehaditoyo, Srie Hartutie (Archives of Business Research, 2018)
The manufacturing company is a company of processing raw materials into products sold into the market. Managers as managers of the company more knowing internal information and prospects of the company in the future than the owners (shareholders). As a Manager, the manager shall be obliged to provide a signal about the condition of the company to the owner. The given signal can be done through the disclosure of accounting information such as financial statements. Basic financial statements provide a lot of information required users to make economic decisions. This research was conducted using a sample of annual reports on the Indonesia stock exchange from the year 2014 to 2016, because the company was pretty much done regression techniques cross section by meeting some of the criteria which may be taken as sample. Sample from a population of 30 companies that meet the criteria of a sample with the limitations of Partial Least Square (PLS). Partial Least Squares is a factor indeterminacy analysis method which is powerful because it doesn’t assume the data is to be with a certain scale and the measurement of the amount of the sample is small. Research results can be concluded that Investment decision, capital structure, free cash flow and earning management effect significantly to Corporate Social Responsibility (CSR) Disclosure on companies listed in Indonesia Stock Exchange (IDX). Investment decision and capital structure no effect on financial performance significantly to companies listed in IDX. Free cash flow and earning management effect significantly to financial performance in company listed in IDX. Investment decision do not affect significantly to the value of the firm at companies listed in IDX. Capital structure, free cash flow and earning management effect significantly to the value of companies listed in IDX. CSR Disclosure effect significantly to financial performance and value of the firm listed in IDX. CSR Disclosure and financial performance effect significantly to the value of the firm at companies listed in IDX.